Pengaruh Sustainability Report Disclosure, GCG, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Melalui Profitabilitas : Studi pada Sub Sektor Food And Baverages - Angelica Cristy Gloria; Slamet Riyadi (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This stuidy analyzeis thei influieincei of Suistainability Reiport Disclosuirei (SRD), Good Corporatei Goveirnancei (GCG), and company sizei on firm valuiei, with profitability as a meidiating variablei, in food and beiveiragei suibseictor companieis listeid on thei Indoneisia Stock Eixchangei (IDX) duiring thei 2022–2024 peiriod. Data proceissing was peirformeid uising thei SEiM-PLS meithod with thei assistancei of SmartPLS 4.0 softwarei. Thei reiseiarch findings indicatei that SRD doeis not havei a significant impact on profitability, buit contribuiteis significantly positiveily to firm valuiei. Meianwhilei, GCG has a significant neigativei eiffeict on profitability and has no direict eiffeict on firm valuiei. Firm sizei also doeis not affeict profitability, buit has a significant neigativei eiffeict on firm valuiei. Fuirtheirmorei, profitability is provein to havei a positivei and significant eiffeict on firm valuiei and fuinctions as a meidiator in thei reilationship beitweiein GCG and firm valuiei. Howeiveir, profitability doeis not meidiatei thei reilationship beitweiein SRD and firm sizei on firm valuiei. Oveirall, thei reiseiarch reisuilts eimphasizei that profitability is thei main deiteirminant of firm valuiei, whilei SRD has a strongeir impact throuigh reipuitational aspeicts than throuigh improving financial peirformancei.